2015
DOI: 10.1080/08959285.2015.1021041
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Uniqueness and Usefulness of Proactive Personality in Organizational Research: A Meta-Analytic Review

Abstract: Using meta-analysis (283 effect sizes from 122 studies), we extend prior qualitative and quantitative reviews of research on proactive personality in a number of meaningful ways. First, we examine the discriminant and incremental validity of proactive personality using meta-analytic regression analyses. Our results reveal that more than 50% of variance in proactive personality is unrelated to the Big Five personality traits collectively. Also, proactive personality accounts for unique variance in overall job p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
82
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(93 citation statements)
references
References 134 publications
5
82
0
6
Order By: Relevance
“…Focusing on the second major goal of this study, our findings suggest that proactive personality constitutes a valid predictor of innovative performance with incremental validity over and beyond the FFM, indicating that this compound trait represents a valid predictor, nonredundant with the big five, when predicting this criterion. These results are in line with previous findings supporting the assumption that this compound trait does represent a dispositional element that is not encompassed in the five‐factor model (Crant, ; Spitzmuller et al, ).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Focusing on the second major goal of this study, our findings suggest that proactive personality constitutes a valid predictor of innovative performance with incremental validity over and beyond the FFM, indicating that this compound trait represents a valid predictor, nonredundant with the big five, when predicting this criterion. These results are in line with previous findings supporting the assumption that this compound trait does represent a dispositional element that is not encompassed in the five‐factor model (Crant, ; Spitzmuller et al, ).…”
Section: Discussionsupporting
confidence: 92%
“…Prior theoretical and empirical work has ascribed a prominent role to this personality disposition for explaining several outcomes with great value for both individuals and organizations. Indeed, previous research has shown that this individual tendency to adopt a self‐starting approach to work and to exhibit proactive behavioral patterns positively impacts several important work outcomes, like career success, leadership, and overall performance (Crant, ; Spitzmuller et al, ). Our study contributes to extend these findings by indicating that this disposition is also relevant to enacting innovative behaviors at work.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, Spitzmuller et al . () report that proactive personality explains incremental variance in these important outcomes after controlling for the effects of the Big Five personality traits.…”
Section: Introductionmentioning
confidence: 99%